2017
DOI: 10.18203/2320-6012.ijrms20172095
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological spectrum of prostatic lesions: a retrospective analysis of transurethral resection of prostate specimens

Abstract: Background: Prostatic diseases like inflammation, benign prostatic hyperplasia and tumors are important causes of mortality and morbidity in males. The incidence of these lesions increases with advancing age. The second most common cancer among males is prostate cancer, next to lung cancer worldwide. Transurethral resection of prostate (TURP) is most frequently preformed surgical procedure in the clinical practice. The purpose of the study is to evaluate histomorphological spectrum of prostate lesions in TURP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 9 publications
9
15
0
Order By: Relevance
“…The finding of HGPIN along with elevated serum PSA is an indication of repeat biopsy and follow up. 4,10,17 In our study 2(2.08%) cases showed HGPIN similar to the study by Sharma A et al 12 who have found 2.04% HGPIN in their studies. Our study showed 8(8.34%) of prostate carcinoma which was similar to other studies.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The finding of HGPIN along with elevated serum PSA is an indication of repeat biopsy and follow up. 4,10,17 In our study 2(2.08%) cases showed HGPIN similar to the study by Sharma A et al 12 who have found 2.04% HGPIN in their studies. Our study showed 8(8.34%) of prostate carcinoma which was similar to other studies.…”
Section: Discussionsupporting
confidence: 91%
“…Benign lesions were common in the age group of 61-70 years whereas malignant lesions were common in the age group of 71-80 years which is in concordance with other studies. 8,11,12 Among the benign lesions nodular hyperplasia of prostate was the most frequent histo-pathological diagnosis in our study accounting for 89.58% cases. Bal et al 13 and Dawam et al 14 observed Nodular hyperplasia of prostate in 87% and 86% cases respectively which is similar to our study.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…2018;7(36):3991-3995, DOI: 10.14260/jemds/2018/891 BACKGROUND Prostate is one of the most commonly affected organs in males. 1 The incidence of prostatic lesions increases with increasing age. 2,3 The most important diseases of prostate are inflammatory lesions (Prostatitis), nodular hyperplasia (Benign prostatic hyperplasia) and carcinoma.…”
Section: Introductionmentioning
confidence: 99%